Pengaruh Kemudahan Penggunaan Teknologi, Kualitas Pelayanan Dan Kepercayaan Terhadap Minat Konsumen Dalam Penggunaan Aplikasi Kasir Ayo SRC - Kurniawati, Rina; Hendri, Nedi; Kurniawan, Angga (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze the ease of use of technology (1), quality of service (2), and trust (3) on consumer interest in using the Kasir Ayo SRC application (Case Study of SRC Wariston Semuli jaya). The population in this research is 135 respondents. The sampling technique in this research used several respondent criteria so as to obtain a sample of 143 respondents. The data in this study used SPSS version 25 with multiple linear regression analysis testing. The results of this study indicate that the Ease of Use of Technology, Quality of Service and Trust partially or simultaneously influence Consumer Interest in Using the Ayo SRC Cashier Application (Case Study of SRC Wariston Semuli jaya)